3D printed porous ceramic scaffolds for bone tissue engineering: a review. (7th July 2017) - Wen, Yu; Xun, Sun; Haoye, Meng; Baichuan, Sun; Peng, Chen; Xuejian, Liu; Kaihong, Zhang; Xuan, Yang; Jiang, Peng; Shibi, Lu
Abstract : This study summarizes the recent research status and development of three-dimensional (3D)-printed porous ceramic scaffolds in bone tissue engineering. Abstract : This study summarizes the recent research status and development of three-dimensional (3D)-printed porous ceramic scaffolds in bone tissue engineering. Recent literature on 3D-printed porous ceramic scaffolds was reviewed. Compared with traditional processing and manufacturing technologies, 3D-printed porous ceramic scaffolds have obvious advantages, such as enhancement of the controllability of the structure or improvement of the production efficiency. More sophisticated scaffolds were fabricated by 3D printing technology. 3D printed bioceramics have broad application prospects in bone tissue engineering. Through understanding the advantages and limitations of different 3D-printing approaches, new classes of bone graft substitutes can be developed.